A Survey of Orientation and Mobility Specialist's Use of Telepractice During COVID-19. (November 2022) - McCarthy, Tessa; Griffin-Shirley, Nora; Siffermann, Eileen
Introduction: This survey sought to establish a baseline for the remote delivery of services (telepractice) by orientation and mobility (O&M) specialists nationwide, which became pervasive in 2020 as a result of the COVID-19 pandemic.Method: An online survey was distributed using professional email lists and then used snowball sampling to obtain a convenience sample. The survey was completed by 66 O&M specialists using telepractice at the time of the survey, the primary criterion for inclusion.Results: Engaging in telepractice was a direct result of the pandemic for 90.77% of the participants. Most professionals' caseloads remained relatively similar to the size they were prior to the pandemic (69.70%), and instruction used a one-on-one model (90.77%). For the most part, professionals were teaching conceptual knowledge rather than actual travel skills using video conferencing software. Most participants indicated they had not received training in telepractice (81.25%). Only 20.00% of participants found telepractice for O&M satisfactory, but 26.16% of participants indicated they would probably continue using telepractice after the pandemic. Most participants (72.13%) were unsure if they were covered by professional liability insurance.Discussion: Most participants were thrust into telepractice and very few received training in telepractice. It is likely that the tools used were tools of convenience. Despite a lack of preparation and lukewarm satisfaction levels, a noteworthy percentage of respondents intend to continue to use telepractice after the end of the pandemic. The liability risks associated with this new model have not been widely assessed.Implications for Practitioners: The most effective tools for O&M telepractice have not yet been identified. Practitioners and researchers can work together to develop and promote promising practices and tools for O&M telepractice. Professional liability should always be investigated before providing services. A tool for professionals to assess risk should be developed.